JUS BUAH JAMBU BIJI MERAH (Psidium guajava L.) DAPAT MENURUNKAN SKOR ATHEROGENIC INDEX OF PLASMA - Anugrah, Riva Mustika; Tjahjono, Kusmiyati; Kartasurya, Martha Irene (Jurnal Gizi dan Pangan, 2017)
Objective of this research was to investigate the effect of red guava juices (Psidium guajava L) on score Atherogenic Index of Plasma (AIP) on toll collectors. Experimental studies with randomized pre-post control group design. Subjects were selected by clustered random sampling. Subjects is Fourthy toll collectors in Semarang. The treatment group received 250 ml red guava juice for 21 days while the control group did not. Measurement of  score AIP  with log(Triglyceride (Test GPO) & High Density Lipoprotein (HDL) (CHOD-PAP)) before and after study, food intake was measured by 3 x 24 recall hours. Data analysis by paired t-test & independent t-test, Wilcoxon & Mann Whitney test  general linear model. The effect of red guava juice to AIP scores was not significant before controlled by age, level of carbohydrate intake and initial conditions(p>0.05). Multivariate analysis showed that the effect of red guava juice to AIP score was significant after controlled by age, carbohydrate intake and initial conditions (p<0.05).